Animal consumption associated with higher intimate partner aggression - Taft, Casey T. (Journal of family violence, 2024)
Purpose: This brief report examined associations between animal consumption and intimate partner aggression in a sample of undergraduates. Two possible explanatory variables for these associations, depressive symptoms and speciesism, were also examined. Methods: Participants included 245 undergraduate students who provided electronic consent and completed a one-time anonymous survey. Results: Results indicated that animal consumption was associated with higher use of physical and psychological intimate partner aggression, even after accounting for other correlates. Animal consumption was also associated with higher speciesism, and speciesism was associated with higher use of physical and psychological intimate partner aggression. Conclusions: Results extend findings from prior studies documenting links between animal consumption and negative outcomes and further suggest that speciesism may play a role in understanding links between animal consumption and intimate partner aggression.